Surface measurement with super-resolution of aluminum thin films by using phase-shifting interferometry - Choque Aquino, Jovanetty Ivan (2021)
Descargue el texto completo en el repositorio institucional del Centro de Investigaciones en Óptica: http://cio.repositorioinstitucional.mx/jspui/handle/1002/1213